DIVERSIDADE E ESTRUTURA GENÉTICA DE Euglossa cordata (Linnaeus, 1758) EM ECOSSISTEMAS DE TRANSIÇÃO NO NORDESTE DO BRASIL. - MARTINS, Denilson Costa (2017)
The Euglossini are an important group of bees responsible for the conservation of forest ecosystems in the Neotropical region, due to the search for chemical compounds by their males. Due to the interaction of Euglossini males and certain groups of plants as a source of aromas, analogous chemicals produced by these plants have become important tools in ecological and genetic studies with these organisms. Since Maranhao is located in a transition zone between the Amazon, Cerrado and Caatinga biomes, it houses a complex mixture of natural landscapes, which can be divided into eight phytoregions. Thus, the present study aimed to study if there is a difference in the genetic structure of Euglossa cordata subpopulations distributed throughout the different landscapes of Maranhão. To answer this question, 337 males of E. cordata were captured in 12 locations in the state of Maranhão and one in the state of Pará. Six microsatellite loci (Egc 18, Egc 24, Egc 26, Egc 30b, Egc 37, Ann2) were analyzed for all samples. At the same time, an analysis of a 601pb segment of the Cit b mitochondrial gene was conducted for 107 males. High values of genetic differentiation were detected for the São Luís sample, either for the microsatellite markers and for the mtDNA (mtST=0,420, AL x SL; mtST= 0,392, HC x S; mtST=0,350 AJ x SL). Also, based on the nuclear markers, the locality of Alcântara also presented significant structuring in some comparisons (ST= 0,20, AL x FN, AL x FN, AL x SL). Two large groups of E. cordata subpopulations were found by Bayesian analysis, placing at one extreme the subpopulation of São Luís and the other one, Alcântara. Based on the results obtained, the association of the genetic diversity of E. cordata to certain phytorregions was discarded. Thus, it is estimated that historical factors allied to anthropic actions for each phyto-region may have influenced the high values of genetic differentiation found. Based on our data, it can be concluded that the subpopulations of E. cordata sampled in the State of Maranhão present important genetic differences that deserve attention when proposing measures for the management and conservation of these populations.